2016
DOI: 10.1016/j.yexcr.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Rab11-FIP1A regulates early trafficking into the recycling endosomes

Abstract: The Rab11 family of small GTPases, along with the Rab11-family interacting proteins (Rab11-FIPs), are critical regulators of intracellular vesicle trafficking and recycling. We have identified a point mutation of Threonine-197 site to an Alanine in Rab11-FIP1A, which causes a dramatic dominant negative phenotype when expressed in HeLa cells. The normally perinuclear distribution of GFP-Rab11-FIP1A was condensed into a membranous cisternum with almost no GFP-Rab11-FIP1A(T197A) remaining outside of this central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…We showed that the RFFL DN mutant failed to affect the internalization, but delayed the recycling of cargoes internalized by CME and CIE, and caused them to accumulate in the clustered ERC. This phenotype is reminiscent of that observed upon EHD1 knockdown (KD) (Jovićet al, 2007;Rapaport et al, 2006), MICALL1 KD (Sharma et al, 2009) and overexpression of class I Rab11-FIP mutants (Schafer et al, 2016;Ducharme et al, 2007) or the MYO5B tail (Hales et al, 2002). Thus, the RFFL DN mutant might compromise the function of these recycling machineries.…”
Section: Discussionmentioning
confidence: 90%
“…We showed that the RFFL DN mutant failed to affect the internalization, but delayed the recycling of cargoes internalized by CME and CIE, and caused them to accumulate in the clustered ERC. This phenotype is reminiscent of that observed upon EHD1 knockdown (KD) (Jovićet al, 2007;Rapaport et al, 2006), MICALL1 KD (Sharma et al, 2009) and overexpression of class I Rab11-FIP mutants (Schafer et al, 2016;Ducharme et al, 2007) or the MYO5B tail (Hales et al, 2002). Thus, the RFFL DN mutant might compromise the function of these recycling machineries.…”
Section: Discussionmentioning
confidence: 90%
“…Manual curation added another 18 proteins with Rab11FIP1, Rab GTPase-binding effector protein 2 (RabEP2), ATP6V1B1, TBC1D13, sorting nexin-24 (SNX24), and synaptogyrin-2 (SYNGR2) being upregulated. Rab11FIP1 is a Rab-interacting protein that is critical for trafficking into early endosomes ( 55 ). TBC1D13, a Rab35-specific GAP that contributes to GLUT4 trafficking, was also upregulated ( 56 ), while CCT8, NISCH, and VAMP5 were downregulated ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As proper vesicular transport is essential for neuronal maintenance and survival, increase of related proteins such as RAB11-FIP which regulates endosomal trafficking [ 39 ] in MSS-LCs but not in both, vulnerable and non-vulnerable PCs of woozy (Figures 6B, 6C , 7E ), makes a neuroprotective role of this protein in MSS-pathogenesis unlikely.…”
Section: Resultsmentioning
confidence: 99%